PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA BERORIENTASI PENDEKATAN INKUIRI PADA MATERI TERMODINAMIKA KELAS XI SMA BERBASIS KURIKULUM 2013 - Mitsalina, Fanny; ', Zulhelmi; ', Fakhruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: This study aims to determine the validity of the development of physics-oriented learning device inquiry approach on thermodynamic materials class XI SMA based on curriculum 2013. Development of tools such as RPP, LKPD and test results learning. The research used in the form of observation method using validation instrument validated by validator, namely 2 lecturers physics FKIP UR and 2 people high school physics teacher. Stages of development of this device starts from the preliminary study, device planning, device development, validation-1, device enhancement, validation-2, and obtained the average number of active results. Data analysis technique used is descriptive analysis. Based on the results of the study, the development of learning tools is valid with the average validity of RPP is 3,25 categories are very high, LKPD is 3,19 categories are high and test result of learning 3,25 with very high category, So that the device is feasible to be used as learning device in school.Key Words: inquiry, development of oriented learning, thermodynamic, curriculum 2013.